Problematizing the paradigms for Teaching Theater to children in the Public Education Network of Santa Maria (RS) (Olhar de Professor, 2022)
In this article we present results of a research carried out from - “Pedagogical and theatrical practices developed with children in the public school system of Santa Maria (RS)” project, that is linked to the Theater Degree course at the Federal University of Santa Maria (UFSM). The main objective was to investigate, through data collection and using semi-structured interviews, the occurrence of artistic and pedagogical practices involving theatrical language in Santa Maria   public school system, as well as to observe where artistic languages take place in the school routine. In this context, the research tried to make a mapping of theater teaching and, then, generat reflections that can contribute to the qualification of the pedagogical-theatrical practices developed in schools. Authors such as: Pereira (2015), Nogueira (2015), Brazil; Marques (2014), Ferreira (2006) among others, subsidize the reflections and help to think about teaching theater in Basic Education.
Keywords: Theater Pedagogy. Theater and Childhood. Teacher Training.